The Urban–Rural Digital Divide in Internet Access and Online Activities During the COVID‐19 Pandemic. - Olson, Kristen; Phillips, Angelica; Smyth, Jolene D.; Stenger, Rachel (Rural Sociology, 2025)
The COVID‐19 pandemic rapidly shifted traditionally in‐person interactions to online. Because rural residents historically have lower rates of broadband internet access, they may have been less likely to conduct activities online than their urban counterparts, reflecting geographic digital inequalities. We examine whether residents of rural areas are less likely than residents of urban areas to have internet access, conduct various activities online, and use videoconferencing software during the COVID‐19 pandemic using a probability survey of Nebraskans conducted in late 2020. We find that rural residents were less likely to have broadband internet access, a pattern that persists after accounting for characteristics of the residents. We also find that rural residents were less likely than their more urban counterparts to order food and groceries online, to stream movies or TV, or to use video conferencing for work and medical care, reflecting likely infrastructure differences in rural areas. Rural residents were also less likely to engage in online education activities, play games online, use social media, or use video conferencing to stay in touch with friends and family, but these geographic differences were explained by resident characteristics, suggesting that these differences in behaviors may be due to preference rather than lacking infrastructure.